Aplikasi Budidaya Rumput Laut Eucheuma cottonii (Weber van Bosse) Dengan Metode Jaring Lepas Dasar (Net Bag) Model Cidaun - Nirwani Soenardjo (Buletin Oseanografi Marina, 2011)
Abstract                 Eucheuma cottonii (Weber van Bosse) is a marine commodity, wich need several particuliarly treatment in the enviroment due to  their cultivation.  The floating cultivation model cidaun using the net for sea grass cultivation is the preference methods to protec the thallus.             The aim of the research is to find the specific growth rate of the Euheuma cottonii at the Bantarpanjang Nusakambangan Island. The eksperiment were done from April to Mei 2004. The research eksperiment based on the randomize with factorial approach 2 x2. The amount of seed (100 gr , 150 gr) and the seagrass distance ( 1,5 m , 2 m ) were aplied as the treatment with 5 replications. The research result show that the specific growth rate reach 4,4 %  , wich justified that the cidaun floating methode can be applied as the cultivation methode.   Key Words  : Eucheuma cottonii, Cultivation, Cidaun floating metode, specific growth rate